2014
DOI: 10.9790/3013-0411-62-66
|View full text |Cite
|
Sign up to set email alerts
|

Study of Bioactive components in Decalepis hamiltonii invitro

Abstract: : Decalepis hamiltonii is a climbing shrub with aromatic tuberous roots distributed in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Polyphenol extracts from Aframomum melegueta, Zingiber officinalis and Myristica fragrans exhibited antiglycation and antioxidant potentials [7]. Muralidhar et al [8] reported anti-radical activity of bioactive components in Decalepis hamiltonii. Also, reactive scavenging activity of the total phenolic content from different parts of Carica papaya was reported by Maisarah et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenol extracts from Aframomum melegueta, Zingiber officinalis and Myristica fragrans exhibited antiglycation and antioxidant potentials [7]. Muralidhar et al [8] reported anti-radical activity of bioactive components in Decalepis hamiltonii. Also, reactive scavenging activity of the total phenolic content from different parts of Carica papaya was reported by Maisarah et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is used as a substitute for Hemidesmus indicus and contains important constituents like quercetin, kaempferol, coumarin and rutin (Anonymous 2002 ). The root also contains an important chemical constituent known as 2-hydroxy-4-methoxybenzaldehyde which is an isomer of vanillin (Thornell et al 2000 ;Muralidhar et al 2014 ;. It possesses bioinsecticidal (George et al 1998 ) and antimicrobial activity (Reddy et al 2002 ).…”
Section: Decalepis Hamiltonii Wight and Arnmentioning
confidence: 99%